Analysis That Affects The Level of Labor Force Participation (TPAK) in The Madura Region - Murni Wati, Ika; Huda, Syamsul (Trunojoyo University of Madura, 2025)
This research investigates the determinants influencing the Labor Force Participation Rate (LFPR) in the Madura area, focusing on variables such as Average Years of Schooling (RLS), District Minimum Wage (UMK), and the Open Unemployment Rate (TPT). The scope of the study includes the regencies of Bangkalan, Sampang, Pamekasan, and Sumenep. Employing a quantitative methodology, the study utilizes panel data regression analysis. The secondary data were sourced from the Central Bureau of Statistics (BPS) spanning the years 2014 to 2023. The analysis revealed that the average duration of schooling (RLS) significantly and positively influences LFPR. Conversely, both the minimum district wage (UMK) and the open unemployment rate (TPT) were found to have no statistically significant impact on labor force participation. These outcomes highlight the critical role of educational enhancement in fostering greater labor market involvement within the Madura region.